Frequency of Extensively Drug Resistant Typhoid Fever in Children Aged 4-16 Years at Pediatrics Unit of Khyber Teaching Hospital - Shah, Syeda Aminah; Amir, Sabahat (Biological and Clinical Sciences Research Journal, 2025)
Extensively drug-resistant (XDR) enteric fever is a growing public health concern, particularly in pediatric populations. The increasing resistance to multiple antibiotics limits treatment options and complicates disease management. Identifying demographic and clinical factors associated with XDR enteric fever is crucial for improving early diagnosis and intervention strategies. Objectives: This study aimed to determine the frequency of extensively drug-resistant (XDR) enteric fever in pediatric patients and identify associated demographic and clinical factors. Methodology: Over six months, a cross-sectional study was conducted at Khyber Teaching Hospital, Peshawar. Children aged 4–16 years with prolonged fever (>40°C for >1 week), abdominal pain (VAS >3), and malaise were included. Diagnosis was confirmed by positive blood cultures for Salmonella enterica serovar Typhi. XDR enteric fever was defined as resistance to ampicillin, chloramphenicol, trimethoprim-sulfamethoxazole, ceftriaxone, and fluoroquinolones. Consecutive non-probability sampling was used, and data were analysed using SPSS version 20. Results: Among 136 participants, the mean age was 9.85 ± 3.76 years, and 57.4% were male. XDR enteric fever was identified in 44.9% (n=61) of cases. Males accounted for 68.9% of XDR cases, while females represented 31.1%. Lower socioeconomic status (49.2%) and rural residence (57.4%) were significantly associated with XDR typhoid (p<0.0001). Prolonged fever duration (>15 days) was observed in 55.7% of XDR cases compared to 25.3% of non-XDR cases (p<0.0001). Conclusion: XDR enteric fever is prevalent among pediatric patients, particularly in males, lower socioeconomic groups, and rural residents. Prolonged fever duration is a significant risk factor.